Chiral and achiral charge-transfer chromophores with a dendralene-type backbone by electronically controlled Cycloaddition/Cycloreversion Cascades - Frank, Brian B.; Kivala, Milan; Blanco, Berta Camafort; Breiten, Benjamin; Schweizer, W. Bernd; Laporta, Philip R.; Biaggio, Ivan; Jahnke, Eike; Tykwinski, Rik; Boudon, Corinne; Gisselbrecht, Jean-Paul; Diederich, Francois (European Journal of Organic Chemistry, 2010)
Chiral and achiral push-pull chromophores have been prepared by cascades of sequential [2+2] cycloadditions of tetracyanoethene (TCNE) and tetrathiafulvalene (TTF) to different oligoynes. Thermal [2+2] cycloaddition of TCNE to donor-substituted alkynes, followed by electrocyclic ring-opening of the initially formed cyclobutenes, affords donor-substituted 1,1,4,4- tetracyanobuta-1,3-dienes (TCBDs). Similarly, TTF reacts with electron-deficient C=C bonds to give the corresponding buta-1,3-diene derivatives, 1,2-bis(1,3-dithiol2-ylidene)ethanes. Thus, achiral [AB]-type oligomers were synthesized from N,N-dialkylanilino (DAA)-substituted tetraynes and hexaynes and chiral [AB]-type oligomers from alkyne-substituted 1,1'-binaphthalenes. The [AB]-type oligomers exhibit complex conformational equilibria in solution, as revealed by H and C NMR spectroscopy. Therefore, the circular dichroism (CD) spectra of the chiral [AB]-type oligomers were measured to investigate whether a preferred conformation of the dendralene-type backbone is induced by the optically active 1,1'-binaphthalene moiety. Electrochemical studies by cyclic voltammetry (CV) and rotating-disk voltammetry (RDV) showed large cathodic shifts of the first oxidation potentials for some of the chiral and achiral [AB]-type oligomers due to sterically enforced rc-deconjugation of the acceptor and donor moieties. The new multivalent systems feature intense, bathochromicaliy shifted intramolecular charge-transfer (CT) bands in the UV/Vis spectra. Extended, donor-substituted TCBDs, which are obtained by mono-addition of TCNE to the hexaynes, exhibit low optical and electrochemical HOMO-LUMO gaps. In addition, a large thirdorder optical nonlinearity was measured for one of these TCBDs by degenerate four-wave mixing (DFWM). © 2010 Wiley-VCH Verlag GmbH & Co. KGaA.